The effect of crowd noise on consumption amount - Ong, Xue Yin (2016)
Research on factors influencing eating behaviours has been abundant. This study examines how social-contextual influences, specifically ambient factors such as crowd noise, would influence consumption amount. As crowdedness is associated with lowered self-control (Fujita, Trope, Liberman, & Levin-Sagi, 2006) and stress (Nicosia, Hyman, Karlin, Epstein, & Aiello, 1979), it is possible that crowd noise would likewise produce higher food intake due to inability to rationally regulate how much one eats (e.g., due to lowered self-control, or emotional eating) when perception of crowdedness is aroused. Thus, it is hypothesised that perceptions of crowdedness would lead to greater consumption of a generally palatable, but unhealthy snack food (Hypothesis 1). Additionally, this effect is hypothesised to be due to heightened anxiety level (Hypothesis 2) and a lower construal level (Hypothesis 3), as associated with perceived crowdedness. Hypothesis 1 was supported whereby the Crowd condition ate the largest amount of chips, followed by the Rain audio condition and then the no-audio control condition. However, the predictions of hypotheses 2 and 3 were unsupported by our data although the general direction of their results aligned with the predictions. These findings suggest that the manipulation of crowdedness simply through auditory channels is sufficient to influence eating behaviours, such that a perception of crowdedness would unknowingly affect an individual to eat more of an unhealthy snack food. Future research should further investigate if perceptions of crowdedness would likewise affect eating rate/speed and also if the findings of this study can be replicated in an actual crowded environment.